ANALISIS PENENTUAN MODEL MERGER-AKUISISI YANG SINERGIS DI BURSA EFEK INDONESIA - Mai, Muhamad Umar (Jurnal Keuangan dan Perbankan, 2016)
The aim of this study was as follow: a) to examine the differences in financial performance and the value of the firm before and after the merger-acquisition of go public company in Indonesia Stock Exchange for the period of 2000-2012;b) to identify and analyze the critical success factors of mergers-acquisitions; c) designing a model of synergistic merger-acquisition. Wilcoxon signed ranks test results showed that the financial performance and the value of the company for certain years are different, in the sense of increased, significantly. The determinant factors of successfull merger-acquisition of 30 synergistic firms, are: a) current ratio and cash ratio was below the industry average; b) debt to asset ratio and debt to equity ratio is above the industry average; c) return on investment and return on equity also above the industry average. Analysis of the 30 synergisticbidders firm shows that the company has a very adequate corporate governance mechanism, namely: a) more than 50% of its stocks owned by other institutions; b) the shares held by the management is below 5%; c) the membership of the board of commissioners and directors have an independent boards and outside directors of more than 30%; and d) the average number of commissioners as many as six people.